PERANAN MEDIATOR DALAM PROSES PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL (Studi Kasus Tentang PHK di Disnaker Provinsi Sumatera Utara) - Fatisia Laia; Soetarto Soetarto; Prietsaweny Riris T. Simamora (JURNAL GOVERNANCE OPINION, 2019)
This thesis discusses the role of the mediator in the process of Industrial Relations Dispute Settlement Process. There are many problems of workers / laborers that in the end do not have a job because of bad relations between workers / employers and businessman. Therefore, in resolving any industrial relations disputes, the role of mediator is needed as a coach in the settlement and development of harmonious and fair industrial relations. This research aims at finding out how the mediator play a role in the process of resolving industrial relations disputes, especially in the Department of Manpower of the North Sumatera Province. Research method used is descriptive qualitative research. Techniques of collecting data used are observation, interview and documentation. The results show that role of mediator in the dispute resolution process of industrial relations at the Department of Labor of North Sumatra province has been effective and implemented in accordance with the regulations of Law No. 13 of 2003 on employment, and Law No. 2 of 2004 concerning the settlement of industrial relations disputes. The role of the mediator can be seen from the implementation of mediation and the tasks of the mediator as the coach, the development and settlement of industrial relations disputes outside the court. Therefore, the mediator has carried out his role in the process of resolving industrial relations disputes.